2002
DOI: 10.2105/ajph.92.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Violence During Pregnancy Among Women With or at Risk for HIV Infection

Abstract: Many HIV-infected pregnant women experience violence, but it is not typically attributable to their serostatus. Prenatal services should incorporate screening and counseling for all women at risk for violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
(21 reference statements)
0
22
0
Order By: Relevance
“…Cohen and colleagues [42] reported no difference in 'lifetime prevalence of domestic violence' between women with HIV and those without, although they reported a strong relationship between CSA and HIV high-risk behaviours. Koenig et al [75] found that the proportion of pregnant women reporting violence was no higher among HIV-positive women than among HIV-negative women.…”
Section: Non-supportive Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cohen and colleagues [42] reported no difference in 'lifetime prevalence of domestic violence' between women with HIV and those without, although they reported a strong relationship between CSA and HIV high-risk behaviours. Koenig et al [75] found that the proportion of pregnant women reporting violence was no higher among HIV-positive women than among HIV-negative women.…”
Section: Non-supportive Studiesmentioning
confidence: 99%
“…Reduced testing or disclosure of status HIV-testing and disclosure of status after testing may be influenced by GBV [73][74][75] (studies from the United States). Fear of violence reduces disclosure of HIV status [76] (study from the United States).…”
Section: Transactional Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined prevalence of IPV during pregnancy and/or postpartum was 10.6 % and did not differ by the women’s HIV status [58, 59]. HIV diagnosis during current pregnancy was actually associated with reduced risk [59].…”
Section: High-income Countriesmentioning
confidence: 99%
“…Routine perinatal care visits offer opportunities for healthcare professionals to screen and refer abused women to effective interventions (78)(79). Although there is importance given to intimate partner violence in pregnancy, a lack of time and clear recommendations for screenings often limit providers of antenatal services asking women specific information (19).…”
Section: The Perspective Of Health Staff and Interventions In Intimatmentioning
confidence: 99%